Combined results of searches for the standard model Higgs boson in pp collisions at s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2012)
Combined results are reported from searches for the standard model Higgs boson in proton-proton collisions at s=7 TeV in five Higgs boson decay modes: γγ, bb, ττ, WW, and ZZ. The explored Higgs boson mass range is 110-600 GeV. The analysed data correspond to an integrated luminosity of 4.6-4.8 fb -1. The expected excluded mass range in the absence of the standard model Higgs boson is 118-543 GeV at 95% CL. The observed results exclude the standard model Higgs boson in the mass range 127-600 GeV at 95% CL, and in the mass range 129-525 GeV at 99% CL. An excess of events above the expected standard model background is observed at the low end of the explored mass range making the observed limits weaker than expected in the absence of a signal. The largest excess, with a local significance of 3.1σ, is observed for a Higgs boson mass hypothesis of 124 GeV. The global significance of observing an excess with a local significance ≥3.1σ anywhere in the search range 110-600 (110-145) GeV is estimated to be 1.5σ(2.1σ). More data are required to ascertain the origin of the observed excess. © 2012 CERN.